Characterization of formal caregivers of dependent elderly people at home in Paraguay: observational study - Mirna Elizabeth Benegas Villamayor; Rutielle Ferreira Silva; Sannya Paes Landim Brito Alves; Maria Antonieta Rubio Tyrrell; Maria do Livramento Fortes Figueiredo (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To characterize the sociodemographic and occupational profile of formal caregivers of dependent elderly people at home in the city of Asunción, Paraguay. Methods: Observational, cross-sectional and descriptive study. It was carried out in households in the urban area of Asunción, Paraguay. The participants were 25 formal caregivers of dependent elderly people at home, selected in a non-probabilistic, snowball fashion. Data was collected from June to December 2022 using a semi-structured interview script and analyzed using descriptive statistics. Results: The majority of caregivers are women (96%), aged between 31 and 45 (68%), born in the interior of Paraguay (52%), with a complete basic education, without a training course for caregivers (100%). Almost all of them had been working for more than three years (76%), paid more than one minimum wage (56%), were dissatisfied with their current salary (84%), had no formal work record (92%), had one day off a week (72%) and, in addition to caring for the elderly, performed domestic activities at home (92%). Conclusion: Understanding the sociodemographic and occupational profile of caregivers is essential for devising effective public policies to improve the quality of life of these professionals and, consequently, the care provided to the elderly.